2019
DOI: 10.3390/su11205693
|View full text |Cite
|
Sign up to set email alerts
|

Family Entrepreneurship and Personal Career Preferences as the Factors of Differences in the Development of Entrepreneurial Potential of Students

Abstract: The purpose of this study is to examine the differences in family entrepreneurship background and personal attitudes of students regarding their future career preferences and its effects on the development of specific dimensions of entrepreneurship potential of a student population. The sample consisted of a student population from Serbia, Bosnia, and Herzegovina as EU candidate countries and Belgium as an EU member country. A sample of 1008 university students from these three countries participated in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Third, sociological factors were much less important than psychological elements for establishing a business, yet entrepreneurial local support background showed some effect. Interestingly, the finding that a person’s family entrepreneurial background is not related to entrepreneurship (in terms of starting a business) contradicts findings of past studies based on students (e.g., Marques et al, 2018 ; Mitrovic Veljkovic et al, 2019 ; Georgescu and Herman, 2020 ; Lee et al, 2021 ) and confirms the notion that actual entrepreneurs need to be included as respondents in entrepreneurship research ( Salmony and Kanbach, 2022 ).…”
Section: Discussion Contributions and Implicationsmentioning
confidence: 51%
See 2 more Smart Citations
“…Third, sociological factors were much less important than psychological elements for establishing a business, yet entrepreneurial local support background showed some effect. Interestingly, the finding that a person’s family entrepreneurial background is not related to entrepreneurship (in terms of starting a business) contradicts findings of past studies based on students (e.g., Marques et al, 2018 ; Mitrovic Veljkovic et al, 2019 ; Georgescu and Herman, 2020 ; Lee et al, 2021 ) and confirms the notion that actual entrepreneurs need to be included as respondents in entrepreneurship research ( Salmony and Kanbach, 2022 ).…”
Section: Discussion Contributions and Implicationsmentioning
confidence: 51%
“…Following the suggestions of Antončič et al (2015) and somewhat less so the findings of Rauch and Frese (2000 , 2007) , we found that the Big Five are the most important for starting companies, with specific motivational personality characteristics also being important, and sociological factors being less important. This study contributes to past research on entrepreneurial personality (e.g., Antončič et al, 2015 ; Murugesan and Jayavelu, 2017 ; Şahin et al, 2019 ; Sahinidis et al, 2020 ; Salmony and Kanbach, 2022 ) and sociological determinants of entrepreneurship (family entrepreneurial background, e.g., Dombrovsky and Welter, 2010 ; Schenkel et al, 2013 ; Marques et al, 2018 ; Mitrovic Veljkovic et al, 2019 ; Georgescu and Herman, 2020 ; Lee et al, 2021 ; local supportive entrepreneurial background, e.g., Reynolds et al, 2005 ; Wong et al, 2005 ; Hisrich et al, 2013 ) by developing the model and providing evidence about the relative importance of psychological and sociological factors for business start-up intentions and behaviors. This study contributes in terms of methodology to research on the Big Five personality characteristics and entrepreneurship (e.g., Murugesan and Jayavelu, 2017 ; Şahin et al, 2019 ; Sahinidis et al, 2020 ; Salmony and Kanbach, 2022 ) by using a sub-sample of actual entrepreneurs and three variables of entrepreneurship.…”
Section: Discussion Contributions and Implicationsmentioning
confidence: 62%
See 1 more Smart Citation
“…Individuals with family members (particularly parents) running firms are said to be more likely to engage in entrepreneurial activity (Hamilton, 2011). Students with entrepreneurial parents have been found to be more influenced toward entrepreneurial activities than those having non-entrepreneurial parents (Veljkovic et al, 2019). Students entering a VCP with an entrepreneurial pedigree should therefore benefit from the visceral learning provided through family-based embeddedness in entrepreneurial activity when initiating new entrepreneurial efforts in the program and therefor more actively choosing an entrepreneurial career after graduation, leading to the following hypothesis:…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…, 2020; Barrett, 2014). Veljkovic et al. (2019) investigated the career preferences of students with entrepreneurial parents vs non-entrepreneurial parents, finding those with entrepreneurial parents are influenced by parents' characteristics and behavior toward entrepreneurial activity.…”
Section: Literature Reviewmentioning
confidence: 99%